Scientific Ethics In Open Systems (Open Academia: Journal of Scholarly Research, 2026)
This article analyzes the concept of scientific ethics within the framework of open systems, focusing on the ethical dimensions of knowledge production, dissemination, and collaboration in contemporary science. Open systems in science—characterized by open access, data sharing, interdisciplinary cooperation, and global research networks—create new opportunities for innovation while simultaneously generating complex ethical challenges. The study examines how principles of scientific ethics, including transparency, accountability, academic integrity, and respect for intellectual property, function under conditions of openness and digitalization. Particular attention is given to ethical risks such as misuse of open data, authorship disputes, unequal access to scientific resources, and the responsibility of researchers in open scientific environments. The article argues that a well-developed ethical framework is essential for maintaining trust, ensuring fairness, and supporting sustainable scientific development in open systems.